TRAUMA - Bond, Lucy, 1983- ([Place of publication not identified])
1 online resource
Keywords: Trauma has become a catchword of our time and a central category in contemporary theory and criticism. In this illuminating and accessible volume, Lucy Bond and Stef Craps: provide an account of the history of the concept of trauma from the late nineteenth century to the present day examine debates around the term in their historical and cultural contexts trace the origins and growth of literary trauma theory introduce the reader to key thinkers in the field explore important issues and tensions in the study of trauma as a cultural phenomenon outline and assess recent critiques and revisions of cultural trauma research Trauma is an essential guide to a rich and vibrant area of literary and cultural inquiry.